Pengaruh Profitabilitas, Leverage, Dan Likuiditas Terhadap Agresivitas Pajak (Studi Empiris Perusahaan Sektor Energi yang terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Matanari, Dodi Antono; Hutagalung, Soly Deo Glorya (Nomico, 2024)
This study aims to examine the effect, profitability, leverage, and liquidity on tax aggressiveness in Energy sector companies listed on the Indonesia Exchange in 2018-2020. The research data is secondary data in the form of financial reports from the company. While the population in this study were all Energy sector companies listed on the Indonesia Stock Exchange in 2018-2020. Sampling in research using purposive sampling method where the population is 72 companies. In accordance with the selected sample criteria, the companies sampled in this study were 24. The data analysis used is multiple linear regression. The results of this study indicate that Profitability, Leverage and Liquidity have no simultaneous effect on tax aggressiveness with a significant value of 0.288, profitability has no effect on tax aggressiveness with a significant value of 0.797, Leverage has no effect on tax aggressiveness with a significant value of 0.467, Liquidity has no effect on tax aggressiveness with a significant value of 0.058.